Efficacy of Topical Applications on Reducing Uremic Pruritus: A Systematic Review - Gabriel Wanda Sinawang; Rohmatul Faizah; Mohamad Roni Alfaqih; Andrik Hermanto (Jurnal Ners, 2019)
Introduction: Uremic pruritus is an unpleasant sensation that has been recognized as a frequent complication in patients with chronic kidney disease. This study was undertaken to determine the effect of topical applications for reducing pruritus.Methods: A systematic review was conducted by searching Science Direct, Scopus and Google Scholar to create an integrative 12 articles review focusing on a 10 year period from 2009 to 2018. The language used was English and the studies focused on pruritus, itching, hydration, chronic kidney disease and where the patient did not undergo a kidney transplant. The articles in this systematic review were experimental studies (pre-experimental, true experimental and quasi-experimental).Results: Most of the findings of the studies showed that a topical application for reducing uremic pruritus (clove oil, almond oil, cromolyn sodium 4%, baby oil, sweet almond oil, vinegar and avenasativa, glycerol and paraffin, sericin cream and chia seed oil) can be used as an adjuvant moisturizing agents for pruritis.Conclusion: Topical applications have a positive effect on itching and decreased pruritus. Topical applications are simple, safe, inexpensive and easily applied, so it can be used on many people.